2013
DOI: 10.1111/1365-2745.12180
|View full text |Cite
|
Sign up to set email alerts
|

Directness and tempo of avian seed dispersal increases emergence of wild chiltepins in desert grasslands

Abstract: Summary1. Seed dispersal is thought to be unpredictable and outside a plant's control. But directed seed dispersal by mutualistic birds can increase probabilities of germination and survival by the non-random deposition of seeds in suitable microhabitats. 2. In the Sonoran Desert grasslands of southern Arizona (USA), bird-dispersed wild chiltepin peppers (Capscium annuum var. glabriusculum) grow in non-random association under bird-dispersed nurse trees and shrubs that serve as perches. We tested the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 38 publications
0
52
0
1
Order By: Relevance
“…Post-dispersal seed predation and density-dependent seedling mortality can be very high under bird perching sites receiving a copious seed rain (Holl 1998, Spiegel and Nathan 2011, Carlo and Tewksbury 2014 and it can slow down plant establishment (Reid and Holl 2013). Post-dispersal seed predation and density-dependent seedling mortality can be very high under bird perching sites receiving a copious seed rain (Holl 1998, Spiegel and Nathan 2011, Carlo and Tewksbury 2014 and it can slow down plant establishment (Reid and Holl 2013).…”
Section: Frugivory and The Initiation Of Forest Successionmentioning
confidence: 99%
“…Post-dispersal seed predation and density-dependent seedling mortality can be very high under bird perching sites receiving a copious seed rain (Holl 1998, Spiegel and Nathan 2011, Carlo and Tewksbury 2014 and it can slow down plant establishment (Reid and Holl 2013). Post-dispersal seed predation and density-dependent seedling mortality can be very high under bird perching sites receiving a copious seed rain (Holl 1998, Spiegel and Nathan 2011, Carlo and Tewksbury 2014 and it can slow down plant establishment (Reid and Holl 2013).…”
Section: Frugivory and The Initiation Of Forest Successionmentioning
confidence: 99%
“…Indeed, in a desert grassland and a temperate heterogeneous system seed deposition was higher under fruiting canopies Carlo and Tewksbury, 2014). Carlo et al (2013) found that long distance dispersal events (distances of 150-700 m) were much more likely to occur under fruiting canopies than non-fruiting.…”
Section: Directed Dispersalmentioning
confidence: 99%
“…Long distance dispersal events are important for plant community stability by maintaining gene flow. Additionally, Carlo and Tewksbury (2014) found that chiltepin pepper (Capscium annuum var. glabriusculum) seeds that were artificially added and arrived there via bird dispersal under dense fruiting shrubs exhibited increased recruitment, leading them to conclude that dispersal of these peppers was directed to favorable microhabitats.…”
Section: Directed Dispersalmentioning
confidence: 99%
“…, Garcia et al. , Carlo and Tewksbury ). Negative and positive outcomes dependent on associations with other species have been termed associational susceptibility and resistance, respectively, and are well documented for plant–herbivore interactions (reviewed by Barbosa et al.…”
Section: Introductionmentioning
confidence: 99%